Optimizing Financing Strategies for Mass Housing Development: A Case Study of Iran - Ghasemi-Honari, Amir-Abbas; Sobhiyah, Mohammad-Hossein (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
The pressing need for housing in Iran is increasingly evident due to population growth and a significant number of young individuals forming families, leading to heightened demand for residential construction. Mass building companies play a crucial role in addressing this demand, yet they require substantial financial resources to achieve the necessary housing construction targets. This study focuses on identifying optimal financing strategies within mass building companies, specifically through a case study of the North East Maskan Investment Company. By reviewing existing literature and conducting qualitative interviews with industry experts, the research explores various financing methods and the criteria influencing their selection. A total of ten financing methods were identified, with two optimal combinations highlighted based on expert opinions. The findings indicate that in inflationary conditions accompanied by a housing market boom, property assets, pre-sales, and construction participation loans are the most utilized methods. Conversely, during inflationary periods with stagnant housing transactions, contractual participation, pre-sales, and barter arrangements dominate. This research aims to enhance the financial strategies of mass building companies, ultimately contributing to increased housing supply in the country.